Academic Senate Minutes 2001-10-11 - Academic Senate:::::::::
Agenda modified and approved. Minutes approved. Report from Chair. Special guest Mayor Jake Mackenzie of Rohnert Park. New Math courses consent item approved. First reading for Living Wage Principles proposal from P. Phillips. Resolution for Lecturer's compensation removed from table. Reports from Vice President of Administration and Finance, Chair of Structures and Functions and Associated Student President.